No small slam: increasing incidents of genitourinary injury from toilets and toilet seats. (14th June 2013) - Glass, Allison S.; Bagga, Herman S.; Tasian, Gregory E.; McGeady, James B.; McCulloch, Charles E.; Blaschko, Sarah D.; McAninch, Jack W.; Breyer, Benjamin N.
<x xml:space="preserve">Abstract</x> Objective To describe the epidemiology of genitourinary (GU) injury from toilets that present to USA Emergency rooms (ERs). Materials and Methods The National Electronic Injury Surveillance System (NEISS) is a stratified probability sample of hospital ER visits for USA consumer product‐related injuries. NEISS was used to estimate total toilet‐ and toilet seat‐related GU injury for the years 2002–2010, as well as to describe demographics and injury characteristics. Analyses were performed using strata, primary sampling units and sample weights to accommodate the complex sample survey design. Data are reported as national estimates with 95% confidence intervals (CIs) provided. Results In all, 13 175 (95% CI 10 185–16 165) GU injuries related to toilets presented to ERs during 2002–2010. The most common mechanism involved crush from accidental fall of toilet seat, described in 9011 (68.4%, 95% CI 6907–11 115) cases. Most crush injuries were isolated to the penis (98.1%). Of crush injuries, 81.7% occurred in children aged 2–3 years and 99.3% occurred in the home. Crush injuries increased over the period 2002–2010 (P = 0.017) by ≈100 per year, ending with an estimated 1707 (95% CI 1011–2402) by 2010. Most patients who sustained toilet‐ and toilet seat‐related GU injuries were treated in the ER and then discharged. Conclusion While penile crush injury related to a toilet seat is an uncommon mechanism of urological injury in children, the number of incidents appears to be rising. These findings support educational efforts and interventions, such as exchange of heavy toilet seats with slow‐close toilet seat technology.